Access to reperfusion therapy and mortality outcomes in patients with ST-segment elevation myocardial infarction under universal health coverage in Thailand - Chulaporn Limwattananon (BMC Cardiovascular Disorders, 2020)
Abstract Background Evidence on access to reperfusion therapy for patients with ST-segment elevation myocardial infarction (STEMI) and associated mortality in developing countries is scarce. This study determined time trends in the nationally aggregated reperfusion and mortality, examined distribution of percutaneous coronary intervention (PCI) utilization across provinces, and assessed the reperfusion-mortality association in Thailand that achieved universal health coverage in 2002. Methods Data on hospitalization with STEMI in 2011–2017 of 69,031 Universal Coverage Scheme (UCS) beneficiaries were used for estimating changes in the national aggregates of % reperfusion and mortality by a time-series analysis. Geographic distribution of PCI-capable hospitals and PCI recipients was illustrated per provinces. The reperfusion-mortality association was determined using the propensity-score matching of individual patients and panel data analysis at the hospital level. The exposure is a presence of PCI or thrombolysis. Outcomes are all-cause mortality within 30 and 180 days after an index hospitalization. Results In 2011–2017, the PCI recipients increased annually 5.7 percentage (%) points and thrombolysis-only recipients decreased 2.2% points. The 30-day and 180-day mortalities respectively decreased annually 0.20 and 0.27% points among the PCI recipients, and they increased 0.79 and 0.59% points among the patients receiving no reperfusion over the same period. Outside Bangkok, the provinces with more than half of the patients receiving PCI increased from 4 provinces of PCI-capable hospitals in 2011 to 37 provinces, which included the neighboring provinces of the PCI-capable hospitals in 2017. Patients undergoing reperfusion had lower 30-day and 180-day mortalities respectively by 19.6 and 21.1% points for PCI, and by 14.1 and 15.1% points for thrombolysis only as compared with no reperfusion. The use of PCI was associated with decreases in 30-day and 180-day mortalities similarly by 5.4–5.5% points as compared with thrombolysis only. A hospital with 1% higher in the recipients of PCI had lower mortalities within 30 and 180 days by approximately 0.21 and 0.20%, respectively. Conclusions Patients with STEMI in Thailand experienced increasing PCI access and the use of PCI was associated with lower mortality compared with thrombolysis only. This is an evidence of progress toward a universal coverage of high-cost and effective health care.